UNIFORM BEAM PROFILES OF 5 CM CONVEX GRIDDED ION-BEAM SOURCE - KOH, SK; SONG, SK; CHOI, WK; JUNG, HJ; GONTCHAROV, L (AMER INST PHYSICS, 1995)
A Kaufman-type 5 cm convex gridded ion-beam source is characterized in terms of angle-resolved ion-beam current density and beam uniformity at various discharge currents, electromagnet currents, and acceleration potentials. (C) 1995 American Institute of Physics.